The Role of Fractional CO2 Laser in Treatment of Keloid and Hypertrophic Scar used Alone and in Combination with Intralesional Steroids - Nadia H. Sahib1 , Mohammed K. Al-hattab2 , Fatin Ahmed Fakhry3 , Ihsan Jara Atiyah4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: The hypertrophic and keloid scars are thick , raised, disfiguring areas of skin with abnormal prolonged inflammatory response of wound healing process and overproduction of collagen. Carbon dioxide (CO2) laser has been used in the treatment of hypertrophic scar and keloids for more than 20 years. Aim of Study: To evaluate the effect of (CO2) laser in treatment of keloid and hypertrophic scar with use of intralesional triamcinolone acetonide (kenacort) 40 mg/ml as adjuvant therapy. Methodology: The study was done on 22 patients in Imam al-Sadiq teaching hospital in Hilla city with dividing the patients randomly in to two groups ,one group treated with four sessions of intralesional corticosteroids and the second group treated with four sessions of intralesional corticosteroids with carbon dioxide laser.